Feasibility of City Development Strategy in Enabling and Regularizing the Informal Settlements, Tabriz metropolis, district 1 - Mohammad shali; jamileh tavakolinia (تحقیقات کاربردی علوم جغرافیایی)
Nowadays, informal settlements has become a common challenge in many of cities particularly in Metropolises .On one hand, it is a spatial manifestation of social and economical inequalities and injustice at the local, regional and national levels. On the other hand it is the result of urban planning deficiency, absence of citizenship and inattention to social and economical needs of low income groups in urban development plans. In this research, in order to develop main strategies for enabling and regularizing Tabriz informal settlements by zoning the district one’s settlements of Tabriz municipality and identifying the low income and vulnerable zones, the social, economical, physical and environmental indicators have been used. Moreover, the data was analyzed by combining GIS and AHP models and three zones were reached. The research shows the socio-economical and environmental separation between vulnerable zones and others. The CDS strategy has been confirmed because of paying attention to participatory and community-based approach for enabling and regularizing informal settlements of Tabriz district one